Radiophobia Overreaction: College of Chiropractors of British Columbia Revoke Full X-Ray Rights Based on Flawed Study and Radiation Fear-Mongering - Paul A. Oakley; Joseph W. Betz; Deed E. Harrison; Leonard A. Siskin; Donald W. Hirsh (SAGE Publishing, 2021)
Fears over radiation have created irrational pressures to dissuade radiography use within chiropractic. Recently, the regulatory body for chiropractors practicing in British Columbia, Canada, the College of Chiropractors of British Columbia (CCBC), contracted Pierre Côté to review the clinical use of X-rays within the chiropractic profession. A "rapid review" was performed and published quickly and included only 9 papers, the most recent dating from 2005; they concluded, "Given the inherent risks of radiation, we recommend that chiropractors do not use radiographs for the routine and repeat evaluation of the structure and function of the spine." The CCBC then launched an immediate review of the use of X-rays by chiropractors in their jurisdiction. Member and public opinion were gathered but not presented to their members. On February 4, 2021, the College announced amendments to their Professional Conduct Handbook that revoked X-ray rights for routine/repeat assessment and management of patients with spine disorders. Here, we highlight current and historical evidence that substantiates that X-rays are not a public health threat. We also point out critical and insurmountable flaws in the single paper used to support irrational and unscientific policy that discriminates against chiropractors who practice certain forms of evidence-based X-ray-guided methods.